EXTRA FLEXIBLE TACTICAL CABLE. - Rigling, Walter S. (1965)
This document is the fifth quarterly progress report of a program to develop a family of lightweight, small diameter, highly flexible, multiconductor cables to meet current and anticipated operational requirements of Army equipment in arctic and tropical environments. The cables shall be air transportable and suitable for use with widely dispersed and highly mobile tactical equipment. Prototype models of a 20 conductor tactical cable and a 25 quad (100 conductors) telephone cable were fabricated. The prototypes are extremely flexible and are considerably smaller and lighter than similar types currently available. (Author)